A novel paradigm for the high-efficient production of phycocyanin from Galdieria sulphuraria. (October 2016) - Wan, Minxi; Wang, Zhenyang; Zhang, Zhen; Wang, Jun; Li, Shulan; Yu, Anquan; Li, Yuanguang
Highlights: High-effective production of phycocyanin can be achieved by SHDP of G. sulphuraria . Final PC content was up to 13.2% of DCW. PC productivity was up to 2209.2 mg/L/d and far surpassed those in other reports. Abstract: A novel cultivation strategy called "Sequential Heterotrophy-Dilution-Photoinduction" was successfully applied in the cultivation of Galdieria sulphuraria for efficient production of phycocyanin (PC). Algae cells were firstly cultivated heterotrophically to achieve high cell density. The maximal dry cell weight of 17.8 g L −1 and maximal biomass productivity of 103.1 mg L −1 h −1 were obtained. Then, a dilution step was applied to obtain a suitable cell concentration and finally these cells were transferred to high light condition for phycocyanin accumulation. During the photoinduction step, cells could accumulate phycocyanin up to 13.88% of dry cell weight in a cultivation period of 8 days. By this technology, total PC productivity far surpassed those reported in all literatures of Galdieria sulphuraria, and was 147-fold and 12-fold of those in photoautotrophic and heterotrophic technologies, respectively. Therefore, this strategy provides a promising approach for high-efficient phycocyanin production from Galdieria sulphuraria to meet its mass cultivation and commercialization application.